Nurses' Satisfaction With Using Nursing Information Systems From Technology Acceptance Model and Information Systems Success Model Perspectives. - Lin, Hsien-Cheng (CIN: Computers, Informatics, Nursing, 2017)
Nursing information systems can enhance nursing practice and the efficiency and quality of administrative affairs within the nursing department and thus have been widely considered for implementation. Close alignment of human-computer interaction can advance optimal clinical performance with the use of information systems. However, a lack of introduction of the concept of alignment between users' perceptions and technological functionality has caused dissatisfaction, as shown in the existing literature. This study provides insight into the alignment between nurses' perceptions and how technological functionality affects their satisfaction with Nursing Information System use through a reductionist perspective of alignment. This cross-sectional study collected data from 531 registered nurses in Taiwan. The results indicated that "perceived usefulness in system quality alignment," "perceived usefulness in information quality alignment," "perceived ease of use in system quality alignment," "perceived ease of use in information quality alignment," and "perceived ease of use in service quality alignment" have significantly affected nurses' satisfaction with Nursing Information System use. However, "perceived usefulness in service quality alignment" had no significant effect on nurses' satisfaction. This study also provides some meaningful implications for theoretical and practical aspects of design.